(untitled) - Nielsen, Henrik Bechmann (Thailand, 2003)
This volume serves a number of purposes. First, it documents more than sevent years of effort through the Danida-AIT project to develop aquaculture education and aquatic resources management in the three countries of Indochina and northeast Thailand.
Keywords: Quản lý nghề cá,Fishery management,Aquaculture